Critical success factors for startups in Malaysia - Tee, Vern Yao (2018)
Critical Success Factors (CSFs) have always been a subject matter of interest in startup-related researches globally. This study takes an approach to understand the CSFs for startups in the Malaysian context, using existing literatures as the backbone to establish a framework of factors. While there are many CSFs proposed by authors across the globe, this study focuses on examining and identifying only those which are most relevant and applicable to startup success in Malaysia.